Sejarah dan Dinamika Kekristenan Jawa di Tegal, Jawa Tengah, 1862-1942 - Kholiludin, Tedi (Indonesian Journal of Theology, 2024)
This article examines the history of Christianity in Tegal as the place where the Nederlandsche Gereformeerde Zendingsvereeniging (NGZV) first worked in Central Java in 1862. Aart Vermeer, whom the NGZV sent, opened a new area in north Tegal and established a Javanese Christian community there. Growth was insignificant until 1904 when Neukirchener Mission, or De Bond van Zendeling van de Salatiga Zending op Java (Salatiga Zending), replaced the NGZV and served Tegal’s Christians until approximately 1942. The data in this historical research came from archives, documents, newspapers, and records related to the research theme. Based on the historical search, it was found that the history and growth of indigenous (Javanese) Christianity in Tegal could not be separated from a place called Muaratua which became the initial landscape. The ministry transitioned from NGZV to Salatiga Zending, which influenced the pattern of service to Christian groups in Muaratua and Tegal in general.